UTILIZATION OF PECEL LELE WASTE AS A RAW MATERIAL OF FISH MEAL - Amsal Rijal Nasution; Suparmi Suparmi; Desmelati Desmelati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Pecel Lele is a deep fried Clarias sp dish. This study aims to obtain fish meal from pecel lele waste by drying, steaming and boiling methods and determine the characteristics of fish meal with the best quality. The experimental design used was a non-factorial Completely Randomized Design (CRD) with 3 replications. The treatments given are drying (L1), steaming (L2) and boiling (L3). The parameters observed were the amount of flour (yield), proximate analysis (moisture, ash, fat, protein content) and chemical analysis (Ca, Mg and Fe content). The results showed that the best pecel leleflour was found in L1 treatment (drying) with the following chemical composition: moisture, ash, protein, fat, calcium and magnesium content was 5.14%, 24.03%, 56.41%, 20.32%, 44.55% 1.43%, respectively. Keywords: Fish meal, proximate analysis, waste